Theoretical approaches to explain interpersonal, prison violence: a unresolved debate in the Chilean penitentiary system - Arévalo Sarce, Alejandro (Revista de Estudios de la Justicia, 2023)
This article analyzes interpersonal prison violence, based on theoretical approaches developed from the mid-20th century to date. We ask ourselves: What are the theoretical developments that explain the core elements of interpersonal, prison violence; and what impact does this have on prison life? The methodology applied was an exhaustive review of the specialized literature. Some of the results indicate that, within the academic debate, the influence of two models stands out: deprivation and importation; while the first postulates that violence is generated as a result of the precarious prison environment, the second highlights the sociocultural characteristics of individuals as the most influential in affecting coexistence between inmates. Nevertheless, these two classic approaches leave aside other explanations of the phenomenon, which delve into the dynamics of administrative control. Finally, some new approaches postulated by criminological research are addressed, such as incarcerated masculinity, prison victimization and, more recently, prison governance, opening the field of study to a more comprehensive look at the phenomenon.